Scalp Necrotizing Fasciitis—A Case Report. Issue 1 (March 2021) - Malik, Richa; Saluja, Satish; Modi, Manoj; Soni, Arun; Kler, Neelam; Chaudhary, Lalit; Kaul, Dinesh
Neonatal necrotizing fasciitis (NF) is an uncommon but often fatal bacterial infection of skin, fascia, and subcutaneous fat. High index of suspicion, appropriate antibiotics, supportive care, and prompt surgical intervention are the cornerstones of management. We report a term neonate with rapidly progressing NF of neck and scalp which complicated to skull osteomyelitis. The baby was managed with intravenous antibiotics and early wound debridement followed by skin grafting. The graft was taken up well and currently the baby is thriving.